Behavioral Neuroscience - Palermo, Sara; Morese, Rosalba (IntechOpen, 2019)
What do we mean by "behavioral neuroscience?" This volume aims at providing an overview of behavioral neuroscience and deepening neuronal mechanisms and brain circuits that regulate the fundamental aspects of human behavior, such as cognitive and emotional functions. It is intended to give the reader the most up-to-date vision of how the interaction between biological mechanisms and neurocognitive processes leads to complex and highly organized behaviors.In recent years the strong impulse given to research on behavioral neuroscience has produced a large literature that documents the high level of complexity of the issue, for which it is necessary to provide a reasoned multidimensional analysis able to integrate the expertise of different disciplines.The book offers an excellent synopsis of perspectives, methods, empirical evidences, and international references. Therefore, it represents an extraordinary opportunity to target neuroscientific hot topics and to outline new horizons in the study of the relationship between brain and behavior.